2007
DOI: 10.7861/clinmedicine.7-2-180
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated defence and the liver

Abstract: -The liver is strategically placed to protect the body against a vast array of potentially harmful compounds. The steps involved include phase I metabolism which makes molecules more reactive and phase II reactions which generally enhance solubility in bile or urine. Recent discoveries have shown how regulation of these reactions is also closely allied to expression of membrane transporters which excrete the products of biotransformation into bile and prevent their reabsorptoion via the intestine. The coordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…23,24 Altered AA profiles may also result from liver defence processes, such as activation of specific defence proteins and production of AA derivatives, which are triggered in order to protect liver cells from injury. [25][26][27] In this study, several identified associations support these assumptions.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…23,24 Altered AA profiles may also result from liver defence processes, such as activation of specific defence proteins and production of AA derivatives, which are triggered in order to protect liver cells from injury. [25][26][27] In this study, several identified associations support these assumptions.…”
Section: Discussionsupporting
confidence: 68%
“…For example in the case of hepatocellular damage, the brain, kidney or skeletal muscles may take over some metabolic processes that cannot be fully supported by the impaired liver . Altered AA profiles may also result from liver defence processes, such as activation of specific defence proteins and production of AA derivatives, which are triggered in order to protect liver cells from injury . In this study, several identified associations support these assumptions.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…*PB0.05 compared with uninfected controls. (Elias & Mills, 2007). Several diseases, including obstructive cholestasis, are associated with a down-regulation of hepatic ABC transporters during the acute phase response to infection (Geier et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Human liver MRP2 expression is upregulated by exposure to lithocholic acid (Elias and Mills, 2007). In healthy gallstone patients, treatment with ursodeoxycholic acid (1 g/day for 3 weeks) does not change significantly MRP2 mRNA or protein expression (Marschall et al, 2005).…”
Section: Regulation Of Hepatic Abcc2/mrp2 Transporters By Xenobioticsmentioning
confidence: 99%